Analysis of Student Learning Outcomes of Grade X SMK on the Exponential Material Based on Emotional Intelligence - Adawiyah, Nur Rabiatul; Roza, Yenita; Maimunah, Maimunah (Jurnal Pendidikan Matematika dan IPA, 2021)
The level of emotional intelligence in students is different, and the learning outcomes obtained from the material are also different. This study was aimed to describe SMK Negeri 1 Mandau students' learning outcomes on the exponential material based on emotional intelligence. The analysis technique used was descriptive qualitative. The subjects analyzed in this study were class X APPS, with 34 students. The data collection's instruments used were questions in the form of essays related to the exponential material and emotional intelligence questionnaires. The study results were obtained from the questionnaires to show the three types of emotional intelligence categories in students; low, medium, and high categories. In varied learning outcomes, some students had a high level of emotional intelligence with satisfactory learning outcomes; some students with moderate emotional intelligence also had satisfactory learning outcomes; other students with moderate emotional intelligence acquired unsatisfactory learning outcomes.